The introduction of mechanical shaft drilling in the Gold Fields Group - B. N. Soutar; R. H. O?Connor (The Southern African Institute of Mining and Metallurgy, 1988)
The paper reviews the introduction 01mechanical shaft drilling into the sinking 01shafts in the Gold Fields Group. A comparison is made between the operating costs 01the drilling rig and those of conventional hand-held machines, and it is concluded that, despite certain disadvantages, mechanical drilling is preferable.